Mapping of GD&T information and PMI between 3D product models in the STEP and STL format. (October 2019) - Hallmann, Martin; Goetz, Stefan; Schleich, Benjamin
Abstract: Increasing specialization of design, manufacturing, assembly, and inspection have fostered the need for sophisticated product documentation practices to allow the clear and unambiguous communication of product information between design and all downstream activities. This need has led to the development of various standards for the exchange of product geometry and related information and particularly to the emergence of STEP as a standard for the exchange of product model data. Though STEP is widely used as an exchange format in design and related domains, other standards and file formats are frequently used for transferring product geometry information from design to downstream activities today, such as the STL (S tandardT esselationL anguage) format, which uses a discrete geometry representation scheme for describing part geometry by an unstructured triangulated surface. However, there exists a gap between STEP, which offers great benefits regarding the documentation of nominal product geometry and product manufacturing information, and the STL format, which offers a discrete geometry representation by triangles. With the aim to close this gap, this paper presents a novel method that allows an automatic mapping of PMI (P roduct andM anufacturingI nformation) and GD&T (G eometricD imensioningand T olerancing) information assigned on the CAD model from STEP files on discrete geometries. The method comprises the interpretation of ISO STEP AP 242 files as well as a novel feature recognition approach. The combined data model, that represents the geometry in tessellated format and includes the GD&T information assigned on the triangulated features, may then serve as an interface model between design, simulation, manufacturing, and inspection and thus contributes to the consistency of product documentation throughout the digital thread in the product life-cycle. The applicability of the method is highlighted using a case study of a car brake system of industrial complexity. In addition, its benefits are underlined by the exemplary application of the method in the context of injection molding simulation and tolerance analysis. Graphical abstract: Highlights: A method for the mapping of GD&T information and PMI is introduced. The information from STEP files is mapped to discrete geometries. A novel feature recognition method for tessellated surface models is presented. The method is applied in the context of computer-aided product development.